2011
DOI: 10.1177/026248931103000601
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependence of Poisson's Ratio of Viscoelastic Elastomer Foam

Abstract: All polymer foams are viscoelastic; for foams used in earplugs, this response is essential to their function. Poisson's ratio was inferred from viscoelastic response of earplug foam in torsion and bending. Poisson's ratio increases with frequency as a result of stress induced air flow. Air within the pores contributes to the overall bulk modulus at high frequency, but not at low frequency at which it easily flows when the foam is deformed. Such behaviour is the opposite of that of solid polymers in which the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In rubbery state GF/PDMS and PDMS foam behave like viscous polymer but the inclusion of graphene does not allow much of the interfacial slippage in polymer so the difference in tan delta values is negligible. longer for the mitigation of applied force, the modulus of porous cells gets relaxed to zero [41] and with the increase in frequency polymer chains become more immobile and energy loss decreases due to decrease in damping. However, after an optimum frequency (13 Hz in this case), tan delta value enhanced with the increase in frequency.…”
Section: Temperature Dependence Of Storage Modulus and Tan Deltamentioning
confidence: 99%
See 1 more Smart Citation
“…In rubbery state GF/PDMS and PDMS foam behave like viscous polymer but the inclusion of graphene does not allow much of the interfacial slippage in polymer so the difference in tan delta values is negligible. longer for the mitigation of applied force, the modulus of porous cells gets relaxed to zero [41] and with the increase in frequency polymer chains become more immobile and energy loss decreases due to decrease in damping. However, after an optimum frequency (13 Hz in this case), tan delta value enhanced with the increase in frequency.…”
Section: Temperature Dependence Of Storage Modulus and Tan Deltamentioning
confidence: 99%
“…Hence, the energy loss increases with the increasing frequency. However, after a certain frequency (here approximately 20 Hz) in the rubbery state, tan delta value fluctuates more due to the presence of air within the porous structure [41] for both GF/PDMS and PDMS foam. Hence, a similar behavior is observed at both the temperatures.…”
Section: Temperature Dependence Of Storage Modulus and Tan Deltamentioning
confidence: 99%
“…5 In addition, frequency-dependent Poisson's ratio of elastomer foam has been revealed to show Zener-type behavior. 6 In this paper, theoretical estimations and experimental determinations of torque and bending moment are presented. Linear viscoelastic properties of PMMA are deduced form our experimental data, and qualitatively compared with predictions from the standard linear solid model.…”
Section: Introductionmentioning
confidence: 99%
“…
1IntroductionThe viscoelastic Poisson's ratio, n(t), is amaterialm echanical property,w hich is closely related to time,t emperature, and strain [1][2][3][4][5][6][7][8][9][10][11].S olid propellants are viscoelastic materials and the Poisson's ratio of solid propellants is an essential input parameter in structural integrity analysis of solid rocket motors (SRM). It has been shown that changes of the Poisson's ratio in micrometer level have great influence on the structural integrity analysis of solid rocket motors [12,13].I ti sc ommonly assumed thatt he Poisson'sr atio is am aterial constant and independent of temperature and strain [14,15].I na ddition, the aging effect on the Poisson's ratio attracts attention in the shelf life predictiono fp ropellants [16].T hus, there are practical as well as theoretical aspects that make it highly desirable to stimulatet he experimental determination of the Poisson's ratio of solid propellants on as ecure analyticalf oundation.Previously,i th as been attempted to use manyd irect or indirect methods measure viscoelastic Poisson's ratio for al ong time.
…”
mentioning
confidence: 99%
“…Measurements of viscoelastic moduli in torsiona nd bending have been conducted at ambientt emperature,2 2 8C, using broadbandv iscoelastic spectroscopy by Dong. The Poisson'sr atio was inferred from frequency-dependent torsional and bendingm oduli [9].Based on the integral transform relationso fs tress relaxation modulus, body modulus and viscoelastic Poisson's ratio, the viscoelastic Poisson's ratio of solid propellants was calculated by using the inversion of Laplace transform and numerical integral [1].H ee tal. built cylindrical motors methodt od eterminet he Poisson'sr atio of solid propellants [5].A ccording to the maximum radial deformations of the perforations of cylindrical motors with two different outer-inner radial ratios after having been cured and drop-[a] H.Abstract:D igital image correlation methodsw ere used for further studieso ft he viscoelastic Poisson'sr atio of solid propellants.…”
mentioning
confidence: 99%